Pre-Service English Teachers’ Lived Experience in Using AI in Teaching Preparation - Karina, Briliana Divani; Kastuhandani, Fidelis Chosa (research, training and philanthropy institution Natural Aceh, 2024)
Pre-service English teachers are expected to integrate technologies to teach in this digital era. Furthermore, AI is rapidly growing and offers teachers to be supported. This phenomenological study explicated pre-service English teachers’ lived experiences in using AIs to support their teaching preparation. In previous studies, less was known about how newcomer educators integrated AI into their pedagogical development. Through in-depth interviews, this study addressed two research questions; What are the pre-service English teachers’ lived experiences in using AI in teaching preparation? How does the AI help the teacher to prepare for their teaching? This study showcased five themes emerging: 1) exploration of AI’s pedagogical potential; 2) emerging pedagogical beliefs and shifting attitudes; 3) intentional integration and innovative lesson design; 4) ethical reflections and responsible AI use; and 5) shifting self-efficacy and confidence. This study explicated how AI utilization experiences mould participants’ pedagogical beliefs, implementation, and perception of technology integration. These findings will help education programmes in preparing candidates and require the TPACK.